Positive Airway Pressure, Mortality, and Cardiovascular Risk in Older Adults With Sleep Apnea - Albert, Albert; Yohana, Yohana (International Medical Journal Corp. Ltd, 2024)
Background: The relationship between Positive Airway Pressure (PAP) therapy and its implications for mortality and cardiovascular risk among older adults with sleep apnea has garnered increasing attention in recent years. This literature review synthesizes findings from various studies to illuminate the multifaceted impacts of PAP therapy on health outcomes in this demographic. Literature Review: The literature on Positive Airway Pressure (PAP) therapy reveals a complex relationship between its use, mortality, and cardiovascular risk in older adults with sleep apnea. The studies reviewed provide substantial evidence that while PAP therapy is a cornerstone treatment for obstructive sleep apnea syndrome (OSAS), its efficacy in improving cardiovascular outcomes and reducing mortality is influenced by factors such as patient adherence and the severity of the condition. Conclusion: In conclusion, the literature collectively underscores the significance of PAP therapy in managing obstructive sleep apnea and its associated cardiovascular risks in older adults. While there is evidence supporting its benefits, particularly in reducing mortality and improving cardiovascular health, the overall effectiveness is heavily contingent upon patient adherence to treatment. Future research is essential to clarify the long-term benefits of PAP therapy and to develop strategies that enhance compliance, ultimately aiming to mitigate mortality and cardiovascular risks in this vulnerable population.